1997
DOI: 10.1172/jci119684
|View full text |Cite
|
Sign up to set email alerts
|

Glucose activates the carboxyl methylation of gamma subunits of trimeric GTP-binding proteins in pancreatic beta cells. Modulation in vivo by calcium, GTP, and pertussis toxin.

Abstract: The ␥ subunits of trimeric G-proteins ( ␥ 1 , ␥ 2 , ␥ 5 , and ␥ 7 isoforms) were found to be methylated at their carboxyl termini in normal rat islets, human islets and pure ␤ [HIT-T15] cells. Of these, GTP ␥ S significantly stimulated the carboxyl methylation selectively of ␥ 2 and ␥ 5 isoforms. Exposure of intact HIT cells to either of two receptor-independent agonists-a stimulatory concentration of glucose or a depolarizing concentration of K ϩ -resulted in a rapid (within 30 s) and sustained (at least up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 76 publications
(105 reference statements)
1
54
0
Order By: Relevance
“…Some of these include the ␥-subunits of trimeric G-proteins and nuclear lamins. Along these lines, we have provided evidence (43) for the direct activation, by glucose, of the carboxylmethylation of ␥-subunits of trimeric G-proteins in islet ␤-cells. It should be noted that the carboxylmethylation is not expected to take place until the candidate ␥-subunit is prenylated.…”
Section: Discussionmentioning
confidence: 78%
“…Some of these include the ␥-subunits of trimeric G-proteins and nuclear lamins. Along these lines, we have provided evidence (43) for the direct activation, by glucose, of the carboxylmethylation of ␥-subunits of trimeric G-proteins in islet ␤-cells. It should be noted that the carboxylmethylation is not expected to take place until the candidate ␥-subunit is prenylated.…”
Section: Discussionmentioning
confidence: 78%
“…Using normal rat islets and clonal β cell preparations, we have been able to demonstrate transient stimulation, by glucose, of the CML of small G-proteins [e.g., Cdc42 or Rap1] and the γ subunits of trimeric G-proteins [19]. Further, we have demonstrated that these proteins are rapidly demethylated in isolated β cell preparations [17]. We have also characterized protein prenyl methyl transferase activity in the islet β cell [20].…”
Section: 1: Evidence For a Requisite Role For The Methylation Of Thmentioning
confidence: 87%
“…It utilizes the intracellular SAM as the methyl donor. In addition, a methylesterase activity that specifically cleaves the methylated residue has also been identified in the islet β cell [17]. Previously, we have identified several carboxylmethylated proteins in the pancreatic β cell.…”
Section: 1: Evidence For a Requisite Role For The Methylation Of Thmentioning
confidence: 98%
See 2 more Smart Citations